SnSe2/FeSe2 Nanocubes Capsulated in Nitrogen‐Doped Carbon Realizing Stable Sodium‐Ion Storage at Ultrahigh Rate. Issue 9 (16th August 2021) - Gao, Xiaoyu; Kuai, Yixi; Xu, Zhixin; Cao, Yongjie; Wang, Nan; Hirano, Shin‐ichi; Nuli, Yanna; Wang, Jiulin; Yang, Jun
Abstract: Metal selenides have attracted increasing attention recently as anodes for sodium‐ion batteries (SIBs) because of their large capacities, high electric conductivity, as well as environmental benignity. However, the application of metal selenides is hindered by the huge volume variation, which causes electrode structure devastation and the consequent degrading cycling stability and rate capability. To overcome the aforementioned obstacles, herein, SnSe2 /FeSe2 nanocubes capsulated in nitrogen‐doped carbon (SFS@NC) are fabricated via a facile co‐precipitation method, followed by poly‐dopamine wrapping and one‐step selenization/carbonization procedure. The most remarkable feature of SFS@NC is the ultra‐stability under high current density while delivering a large capacity. The synergistic effect of dual selenide components and core‐shell architecture mitigates the volume effect, alleviates the agglomeration of nanoparticles, and further improves the electric conductivity. The as‐prepared SFS@NC nanocubes present a high capacity of 408.1 mAh g −1 after 1200 cycles at 6 A g −1, corresponding to an 85.3% retention, and can achieve a capacity of 345.0 mAh g −1 at an extremely high current density of 20 A g −1 . The outstanding performance of SFS@NC may provide a hint to future material structure design strategy, and promote further developments and applications of SIBs. Abstract : SnSe2 /FeSe2 nanocubes capsulated in nitrogen‐doped carbon (SFS@NC) are fabricated, which exhibit superb rate capability of 408.1 mAh g −1 after 1200 cycles at 6 A g −1, corresponding to an 85.3% retention. The synergistic effect of dual selenide components and core‐shell architecture mitigates the volume effect, alleviates the agglomeration of nanoparticles, and further improves the electric conductivity.